DEHUMANIZING TECHNOLOGY EFFECT FIGURED IN TOUCHSCREEN POEM BY MARSHALL DAVIS JONES - PERDANA, IQBAL FEBRIAN (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Poetry, Semiotics, Sociology of Literature, Human Nature, Dehumanization, Technology. Poetry is one of literary works that represents phenomena happening in society. A poet usually uses a poem as a media to describe the condition of his or her society by using specific words picturing the phenomena. One of the phenomena happening in society nowadays is technology development. Even though technology can help human to ease their daily life, it can also change all of their social aspects, which can make themselves deprive their qualities. Later, this phenomenon is usually called as dehumanization. This study aims to find out the effect of technology development toward culture and human nature as pictured in Touchscreen poem. This research analyzes the dehumanization effect of technology toward culture and human nature by using Semiotics and Sociology of Literature theory. Peirce’s semiotics theory of signs is used to reveal the meaning of Touchscreen poem. For further analysis on the human social aspects, the writer uses Sociology of Literature to analyze the aspects of human life those are affected by technology development. The result of the research shows that in Touchscreen poem, the poet pictures the dehumanization phenomenon by technology affecting culture aspects, such as lifestyle, social status, and communication. Besides, that phenomenon also affects human nature, in the relation to human feelings. By covering those aspects, technology changes modern people style of living. They usually buy high price technology device to symbolize their social status and to communicate with otherwithout real social contact. Later, the lack of contact decreases human feeling qualities, resulting effects to other people and nature. For the next researchers who look for new object to be analyzed, they are suggested to use Touchscreen poem that is analyzed by using postmodernism–hyper reality theory, because people nowadays usually have more attention to the World Wide Web than the real world. It means that those people have become more involved with the hyperreal world and less with the physical real world. People nowadays likely chose to stay online and update their daily status in social media rather than communicate directly with their family or friends.